An Understanding of the Photocatalytic Properties and Pollutant Degradation Mechanism of SrTiO3 Nanoparticles - Silva, Luis F. da [UNESP]; Lopes, Osmando F.; Mendonca, Vagner R. de; Carvalho, Kele T. G.; Longo, Elson [UNESP]; Ribeiro, Caue; Mastelaro, Valmor R. (Wiley-Blackwell, 2016)
Strontium titanate nanoparticles have attracted much attention due to their physical and chemical properties, especially as photocatalysts under ultraviolet irradiation. In this paper, we analyze the effect of heating rate during the crystallization process of SrTiO3 nanoparticles in the degradation of organic pollutants. The relationship between structural, morphological and photocatalytic properties of the SrTiO3 nanoparticles was investigated using different techniques. Transmission electron microscopy and N-2 adsorption results show that particle size and surface properties are tuned by the heating rate of the SrTiO3 crystallization process. The SrTiO3 nanoparticles showed good photoactivity for the degradation of methylene blue, rhodamine B and methyl orange dyes, driven by a nonselective process. The SrTiO3 sample with the largest particle size exhibited higher photoactivity per unit area, independent of the molecule to be degraded. The results pointed out that the photodegradation of methylene blue dye catalyzed by SrTiO3 is caused by the action of valence band holes (direct pathway), and the indirect mechanism has a negligible effect, i.e. degradation by O-2(-center dot) and (OH)-O-center dot radicals attack.